School principals’ proposals for preventive actions to improve mental health - Roger Persson; Ulf Leo; Inger Arvidsson; Kerstin Nilsson; Kai Österberg; Carita Håkansson (Archives of Public Health)
Abstract Background School principals face a demanding work situation that puts them at risk for stress-related poor mental health. Ideally, preventive actions should be based on knowledge about the underlying notions that motivate action. However, knowledge about prevention areas and suitable initiatives for school principals is scarce or lacking, leaving key stakeholders without the overview necessary for effectively engaging in preventive actions. Objective To describe school principals’ proposals for suitable target areas and preventive actions that may decrease their workload and improve their mental health. Methods An aggregated analysis was conducted using data from a larger project involving two national surveys (N = 2871), nine group interviews (N = 39), and eleven workshops (N = 270). The project was designed a priori to examine multiple questions, including identifying target areas and collecting proposals for preventive actions. Results Forty-four proposals for preventive actions spanning various levels and six major themes were identified: Role demands and role conflicts (8 proposals); Organizational support (6 proposals); Resources and resource allocation (3 proposals); Continued professional development and coaching (2 proposals); The principal as a coworker (6 proposals); Personal actions (19 proposals). Conclusions The considerable number of proposals and their content reveal that preventive actions are needed at all levels of the educational system and that the school principals’ personal resources matter for improving their work situation and mental health. The pattern of results also underscores the importance of having a deep understanding of what problems to address, and in which context they unfold, before engaging in preventive actions.